Mobile health-based remote interaction management intervention for patients with low anterior resection syndrome: study protocol for a randomised controlled trial - Ting Wang; Peng Zhou; Min Fu; Shihui Yu; Shaohua Hu; Hongye He; Xueying Pang; Danqiao Yin; Degang Zhu (BMJ Open)
Introduction Low anterior resection syndrome (LARS) involves bowel dysfunction after sphincter-preserving surgery for rectal resection that significantly impacts patients’ quality of life (QoL). The improvement of LARS largely depends on patient self-management behaviour; however, insufficient information about supportive care and weak awareness of self-management lead to poor self-management behaviour. Motivational interviewing (MIs) explore and change patients’ ambivalence during the conversation, thereby changing and maintaining healthy behaviours to enhance effective participation. In recent years, mobile health has been widely used in clinical practice, providing continuous information support and remote interaction. However, current online information on LARS is suboptimal, websites are highly variable, important content is often lacking and the material is too complex for patients. Therefore, this study will evaluate the impacts of a remote LARS interaction management intervention based on a WeChat applet (‘e-bowel safety’) and MIs on patients with LARS.Methods and analysis This study will be a single-blind, two-arm randomised controlled trial involving patients with LARS in three tertiary grade A general hospitals who will be randomised into two groups. The intervention group will use the ‘e-bowel safety’ applet and the intervention team will conduct a monthly MI about syndrome management. The control group will receive an information booklet that contains the same information as that provided in the ‘e-bowel safety’ informational module. The intervention will last for 3 months, followed by 3 months of follow-up. The primary outcome will be global QoL; the secondary outcomes will include bowel function, social support, self-management measured at the baseline, 3 months and 6 months for three times and patients’ thinkings at the end of the intervention (at 3 months).Ethics and dissemination Ethics approval was granted by the Clinical Medical Research Ethics Committee of the First Affiliated Hospital of Anhui Medical University (PJ2022-07-53).Trial registration number Chinese Clinical Trial Registry (ChiCTR2200061317).